Structural barriers to screening for and treatment of cervical cancer in Peru - Paz-Soldán, Valerie A (2012)
Through in-depth interviews with 30 key informants from 19 institutions in the health care system in four regions of Peru, this study identifies multiple barriers to obtaining cervical cancer screening, follow-up, and treatment. Some facilities outside Lima do not have the capacity to take Pap smear samples; others cannot do so on a continuing basis. Variation in procedures used by facilities and between regions, differences in women’s ability to pay, as well as varying levels of training of laboratory personnel, all affect the quality and timing of service delivery and outcomes. In some settings, perverse incentives to accrue overtime payments increase the lag time between sample collection and reporting back of results. Some patients with abnormal results are lost to follow-up; others find needed treatment to be out of their financial or geographic reach. To increase coverage for cervical cancer screening and follow-up, interventions are needed at all levels, including an institutional overhaul to ensure that referral mechanisms are appropriate and that treatment is accessible and affordable. Training for midwives and gynaecologists is needed in good sample collection and fixing, and quality control of samples. Training of additional cytotechnologists, especially in the provinces, and incentives for processing Pap smears in an appropriate, timely manner is also required.